Implementation of Lean Management Principles for Operational Efficiency - Hastono, H.; Affandi, Azhar; Sunarsi, Denok (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2024)
This article explores the implementation of Lean Management principles to improve operational efficiency in organizations. Lean Management, with its roots in the Toyota production system, focuses on reducing waste and increasing value for customers. The main goal of implementing this method is to create a more efficient work process, reduce costs, and improve the quality of products or services. This article begins with a brief introduction to Lean Management, including its origins and philosophy, as well as the importance of operational efficiency in the current era of globalization. In the core section, this article details the key steps in implementing Lean Management, starting from Value Stream Mapping to identify inefficiencies, creating Flows to optimize processes, implementing a Pull System to avoid overproduction, to implementing Kaizen for continuous improvement. Each step is explained with theory and illustrated through applicable examples, showing how this theory is applied in real business practice. Next, this article outlines the significant benefits of implementing Lean Management, including increased cost and time efficiency, better product or service quality, higher customer satisfaction, and increased organizational flexibility and adaptability. A real case study is presented to illustrate the transformation achieved through the application of Lean principles. The conclusion of the article summarizes the long-term benefits of implementing Lean Management and emphasizes the importance of innovation and adaptation in operational management. This article concludes with recommendations for organizations seeking to implement Lean Management, as well as providing additional resources for readers interested in exploring further.